KONSUMSI AL-GHAZALI: PENGGUNAAN PAYLATER UNTUK KEBUTUHAN ATAU KEINGINAN? - Annisa, Raihan Cahya; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The research aims to find out whether the perceived ease of use, lifestyle, and income factors influence the use of paylater and their influence towards the consumptive behavior of Gen Z in Malang City. This research will also prove al-Ghazali's theory of consumption regarding whether the use of this paylater is used for needs or just desires. The analytical method used in this study is partial least squares for data processing and analysis. The results of this study indicate that two factors significantly influence interest in using paylater, namely perceived ease of use and lifestyle. In addition, this study also found that the use of paylater has an impact on consumptive behavior. The findings have implications for both practitioners and researchers, for looking at Gen Z consumptive behavior and its relation to Al Ghazali's theory of consumption.